Respiratory bellows‐gated late gadolinium enhancement of the left atrium. Issue 5 (29th November 2012) - Peters, Dana C.; Shaw, Jaime L.; Knowles, Benjamin R.; Moghari, Mehdi Hedjazi; Manning, Warren J.
<x xml:space="preserve">Abstract</x> Purpose To compare bellows‐gated late gadolinium enhancement (LGE) with standard navigator‐gated (NAV‐gated) LGE for left atrial (LA) imaging, to eliminate the inflow artifacts associated with NAV‐gating. Materials and Methods Eleven subjects, including six patients with atrial fibrillation (AF), were imaged with a 3D free‐breathing NAV‐gated and bellows‐gated LGE. Motion compensation was compared by blinded grading of image sharpness and motion ghosting (0 = worst, 2 = best). Inflow artifacts in the right inferior pulmonary vein (RIPV) and right superior PV (RSPV) were characterized on the same scale (0 = none, 2 = prominent). In patients, each PV was divided into four quadrants circumferentially in order to assess agreement about scar presence on both image sets. Results Respiratory compensation was not different (1.7 ± 0.5 vs. 1.6 ± 0.5, sharpness, 1.6 ± 0.5 vs. 1.6 ± 0.5, ghosting, P = NS) for bellows‐ and NAV‐gated images. For NAV‐gated LGE, inflow artifacts were more prominent in the RSPV than the RIPV (1.2 ± 0.8 vs. 0.7 ± 0.5, P = 0.046). Visually, inflow artifacts both obscured and mimicked the true scar. Disagreement on the presence of scar was found in 18% of the assessed quadrants, with 25% disagreement for RSPV quadrants (P = 0.01). Conclusion Bellows‐gated LGE provides similar respiratory compensation as NAV‐gating, without inflow artifacts, leading to improved assessment of scar presence. J. Magn. Reson. Imaging 2013;38:1210–1214. © 2013 Wiley Periodicals, Inc.